ETIKA KOMUNIKASI ISLAM DALAM LAYANAN INFORMASI DI MEDIA SOSIAL - Suci Suliyanti; Tahir; Fuad Fansuri (Lembaga Kajian dan Pemberdayaan Mahasiswa UIN Prof. KH. Saifuddin Zuhri Purwokerto, 2024)
The rising influence of social media has led to an increasing need for effective communication strategies across different sectors. This research examines the application of sharia-based communication ethics in providing information services through social media, particularly focusing on their impact on community engagement and local tax administrators. A mixed-methods approach is used, integrating qualitative interviews with social media analysis to assess the effectiveness of communication ethics such as qaulan baligha, qaulan syadida, qaulan layyina, qaulan karima, qaulan ma'rufa, and qaulan mashura. The findings reveal that while targeted and persuasive communication models (qaulan baligha) are implemented, overall user engagement remains low. Transparent communication (qaulan syadida) improves public trust, while respectful and courteous communication (qaulan layyina and qaulan karima) promotes positive interaction. Additionally, clear and easily understandable communication (qaulan ma'rufa and qaulan mashura) supports efficient information delivery. These results suggest that incorporating these communication ethics can enhance both information dissemination and public engagement on social media platforms.